THE EFFECT OF PROBLEM BASED LEARNING MODEL TO THE STUDENT CREATIVE THINKING ON CELL MATERIAL - Hapida, Yustina; ., Munir; ., Syarifah; ., Marleni (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
Problem based learning model is a learning that is done by confronting students on real problems in everyday life so that students can develop their own knowledge in solving problems and seeking various solutions, which encourages students to think creatively. This study aims to determine the implementation of learning by using problem-based model to determine the effect of model problem based learning on students' creative thinking ability on cell material in the classroom. The design of this research is using Pretest-Posttest Only Control Design design with Quasi-Experimental design method. The sample of the study is 84 students. Based on the results of the analysis, students' creative thinking ability shows that the implementation of learning by using problem-based learning model is better than the control class. The result of this research can be concluded that the problem based learning model influences the students' creative thinking ability. For students, in following the learning with Problem Based Learning model is expected to improve students' creative thinking ability by directly involved in learning in the classroom. For teachers, it is expected to use Problem Based Learning model in learning activities in order to create an active and creative learning process. For schools, it is expected to provide advice and motivate teachers to use appropriate and varied learning models in the learning process. For further research, it is expected to use Problem Based Learning model in other materials, and also can use other learning model. Keywords : cell, creative thinking, learning, PBL